Akuntansi Pesantren Berbasis Kewirausahaan Berdasarkan SAK ETAP Dengan Aplikasi Myob - Vina Riskiya , Amalia; Nilasari, Yekti; Patra Pertiwi, Triani (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama’ah, 2025)
Financial ratio analysis is a crucial method for evaluating the performance of entities, as employed in this study to measure the effectiveness, efficiency, and self-reliance ratios of Panguragan Lor Village, Panguragan District, Cirebon Regency. This research adopts a quantitative approach with purposive sampling involving 24 representatives from village officials and community members knowledgeable in financial analysis. Data were collected through observation, questionnaires, and documentation. Data analysis employed descriptive analysis, multiple linear regression, t-test, f test, and coefficient of determination using SPSS version 25 software. The study findings reveal significant improvements in the values of effectiveness, efficiency, and self-reliance ratios sequentially. Both the F-test and T-test demonstrate a positive and significant influence of the effectiveness ratio on the village’s financial performance. The calculated coefficient of determination indicates that 41.5% of the variation in financial performance can be explained by the variables of effectiveness, efficiency, and self-reliance examined in this study. Meanwhile, approximately 58.5% of the remaining variation may be attributed to other factors not considered in this research. This study provides deep insights into the importance of financial ratio analysis in assessing village financial performance and its implications for decision-making and policy development aimed at improving village financial management in the future.